(Using the Quotient Rule) -> Show that the derivative of (cosx)/(sinx) is (-1)/(sinx).

This question is a typical example aimed to test the student's understanding of the quotient rule, a technique which is used very often in calculus problems. Answer: For a function f(x) = cosx/sinx = u/v, let u = cosx and v =sinx Now, du/dx = -sinx and dv/dx = cosx d/dx (f(x)) = ( v du/dx - u dv\dx ) \ v^2 <- Quotient rule Applying the quotient rule: d/dx (cosx/sinx) = sinx(-sinx) - cosx(cosx) / sin^2(x) = -sin^2(x) - cos^2(x) / sin^2(x) = -1(sin^2(x) + cos^2(x)) / sin^2(x) (Using the fact: sin^2(x) + cos^2(x) = 1) = -1 / sin^2(x) as required. Method: > First assign values to u and v. > Then differentiate u and v. > Apply the quotient rule. > Simplify expression using trigonometric identity.

Answered by Mark H. Maths tutor

14653 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

An ellipse has the equation (x^2)/4 + (y^2)/9 = 1. Find the equation of the tangent at (-6/5 , 12/5)


R=1000e^-ct , it takes 5730 years for half of the substance to decay a. find the number of atoms at the start of the decay. b. calculate the number of atoms left when t=22920. c. sketch the function.


Given a table showing grouped data and the frequency of each class, find the median Q2


Given that y=(4x+1)^3*sin(2x) , find dy/dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences